Prevalence of shoulder pain in competitive archery - Kaur Grover, J.; Kumar Sinha, A. G. (Asian Journal of Sports Medicine, 2017)
Background: Studies reporting prevalence of shoulder pain in competitive archery are limited. The purpose of this study was to document the features of shoulder injuries and determine the prevalence of shoulder pain in Indian competitive archers.